Enhancing Loyalty through Engagement, Experience, and Social Media Marketing - Shanti Handayani; Andry Andry; Noviermi Noviermi (International Forum of Researchers and Lecturers, 2026)
Tambak Mother and Child Hospital experienced a 15% decline in patient visits in 2024, involving both new and returning patients. This decline highlights the importance of patient loyalty, as loyal patients are more likely to continue using hospital services and recommend the hospital to others. This study aims to examine the effects of social media marketing and patient experience on patient loyalty, with patient engagement as a mediating variable.This study employed a quantitative causal research design. Data were collected from 190 patients using purposive sampling. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was used to analyze the relationships among variables.The results indicate that social media marketing, patient experience, and patient engagement simultaneously have a significant effect on patient loyalty. Individually, social media marketing, patient experience, and patient engagement each show a positive and significant influence on patient loyalty. In addition, social media marketing and patient experience positively affect patient engagement. The findings further confirm that patient engagement mediates the relationships between social media marketing and patient loyalty, as well as between patient experience and patient loyalty.These findings suggest that hospital management should strengthen interactive communication through social media platforms, particularly Instagram, improve service efficiency by increasing staffing levels, and enhance service quality through friendly staff behavior and faster service processes. Future research is recommended to include broader samples across Mother and Child Hospitals and incorporate additional variables such as patient satisfaction, service quality, and trust.